An exploration of Indonesian emerging adults non-suicidal self-injury (NSSI) functions and religious coping - Nadya Elvina; Bintari, Dini Rahma (Penerbit Universiti Kebangsaan Malaysia, 2021)
Religious coping may influence non-suicidal self-injury (NSSI) engagement in emerging adults. However, the role of religious coping in influencing the functions served by NSSI is unknown. This exploratory, non-experimental, cross-sectional study investigated the relationship between religious coping and NSSI functions among emerging adults. Indonesian emerging adults (N = 311) aged 18–29 years old, recruited using non-probability sampling methods, participated in an online questionnaire which included measures of positive and negative religious coping (the Brief RCOPE) and NSSI severity and functions (the Non-Suicidal Self-Injury Function Scale). Negative religious coping significantly correlated with NSSI severity (r(297) = .26, p < .001), while positive religious coping did not (p > .05). Moreover, negative religious coping significantly predicted the use of NSSI to incite desirable emotions (β = 0.35, p < .001), reduce aversive feelings (β = 0.43, p < .001), facilitate help-seeking (β = 0.48, p < .001), and evade social situations (β = 0.51, p < .001). Meanwhile, positive religious coping was not a significant predictor of any of the NSSI functions (p > .05). Thus, practitioners should be more aware of the presence of negative religious coping among emerging adults as this study highlights its harmful nature.